Narrative Risk Communication as a Lingua Franca for Environmental Hazard Preparation. Issue 1 (2nd January 2022) - Raile, Eric D.; Shanahan, Elizabeth A.; Ready, Richard C.; McEvoy, Jamie; Izurieta, Clemente; Reinhold, Ann Marie; Poole, Geoffrey C.; Bergmann, Nicolas T.; King, Henry
ABSTRACT: Incorporating narrative elements into risk communication may encourage preparation for environmental hazards in ways that scientific language alone does not. We integrate narrative theory, narrative persuasion, and risk theories into a Narrative Risk Communication Framework and then assess the effectiveness of character selection as a narrative mechanism in scientific risk communication as compared to conventional science messaging alone. We utilize a survey experiment with residents along the flood-prone Yellowstone River in Montana and analyze the resulting data with a parallel and serial mediation statistical model. We find that positive affective response mediates the influence of narratives featuring hero character language. Positive affective response appears to overcome the risk perception paradox both by circumventing rational analysis of risk and by shaping risk perception. Overall, the results suggest that inspirational hero language is superior to language of fear or victimization in encouraging preparation – an important lesson for practitioners working to help citizens prepare for environmental disasters.